Optimizing Visual Identity City Branding Grobogan Through Design Thingking Approach Based on Cakra Manggilingan Concept - Romadhon, Mohammad Aditia Gilang; Yunianto, Ipung Kurniawan (Universitas Negeri Medan, 2025)
Grobogan Regency is building a positive image and promoting the region's superior potential through the Javanese philosophy concept